On the Fractional Variable Order Thermostat Model: Existence Theory on Cones via Piece-Wise Constant Functions. (24th March 2022) - Rezapour, Shahram; Souid, Mohammed Said; Bouazza, Zoubida; Hussain, Azhar; Etemad, Sina
Abstract : In the current manuscript, we intend to investigate the existence, uniqueness, and the stability of positive solution in relation to a fractional version of variable order thermostat model equipped with nonlocal boundary values in the Caputo sense. In fact, we will get help from the constant piece-wise functions for transforming our variable order model into an auxiliary standard model of thermostat. By Guo-Krasnoselskii's fixed point theorem on cones, we derive the required conditions ensuring the existence property for positive solutions. An example is illustrated to examine the validity of the observed results.